The Influence of Leadership, Work Culture, and Competence on the Performance of Village Fund Managers - Agustina Mogi; Ninik Anggraini (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Village development is an important aspect to promote equitable welfare, empower local communities, and improve governance. This study examines the influence of transformational leadership, work culture, and competence on the performance of Village Fund managers, with work commitment as a mediation variable and government policy as a moderation variable. A quantitative approach with explanatory design is used. The population consists of the managers of the Village Fund, including the village head, secretary, treasurer, and other officials directly involved in the management of the fund. A sample of 360 respondents was selected using stratified cluster sampling to ensure representation across regions and roles. Data were collected through a structured questionnaire based on a validated theoretical construct and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0 software. The findings show that competence, leadership, and work culture significantly affect the work commitment and performance of Village Fund managers. Work commitments are confirmed as significant mediators, while government policies effectively moderate the relationship between commitment and performance.